2012
DOI: 10.4236/jcpt.2012.24023
|View full text |Cite
|
Sign up to set email alerts
|

Pyro and Kinetic Studies of Barium Oxalate Crystals Grown in Agar Gel

Abstract: Single crystals of barium oxalate have been grown using gel method at ambient temperature. Thermal characteristics and kinetic parameters of barium oxalate crystals were determined by thermo-gravimetric (TG) analysis under non-isothermal heating conditions. The pyrolysis experiments were performed with increasing temperature up-to 600℃ at heating rate of 5℃, 7℃ and 10℃ in nitrogen gas atmosphere. The pyrolysis curve showed that loss of mass took place mainly in the range of 220℃ - 400℃. At higher temperature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 23 In the process of decomposition, the dynamic Gibb's free energy change may be due to the fundamental criteria of spontaneous reaction. 24 The negative scale of entropy was assigned to the highly ordered structure of the activated complex rather than to that of its reactants. 25 The endothermic nature of dissociation processes were authenticated by the positive value of enthalpy.…”
Section: Resultsmentioning
confidence: 99%
“… 23 In the process of decomposition, the dynamic Gibb's free energy change may be due to the fundamental criteria of spontaneous reaction. 24 The negative scale of entropy was assigned to the highly ordered structure of the activated complex rather than to that of its reactants. 25 The endothermic nature of dissociation processes were authenticated by the positive value of enthalpy.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic and thermodynamic parameters of degradation phases were calculated using Coats and Redfern method [16,17]. Eqns.…”
Section: Thermogravimetric (Tg) Studiesmentioning
confidence: 99%
“…[ 6,7 ] Mostly, the metal oxalate crystals were grown through the gel method by single diffusion technique and reported that the gel method was suitable for the growth of well‐developed and notably transparent crystals of pure metal oxalates. [ 8–11 ] Glycine (NH 2 CH 2 COOH) is the simplest amino acid and exhibits three polymeric crystalline forms α, β, and γ. [ 12,13 ] The glycine exists as zwitterions in solid and solution but as a neutral molecule in the gaseous state.…”
Section: Introductionmentioning
confidence: 99%